Potret Hidup Orang Jawa dalam Novel "Prau Gethek Nyabrang Jaladri" Karya Soekirman - Arie Toursino Hadi; Melinda Sariningsih; Nanny Sri Lestari (Journal on Education, 2023)
A literary work has often used a medium for describing a behavior or attitude of character who played a role in the story. The focus of this study base on behavior reflected by the cast, which constructs through its life experience. "Prau Gethek Nyabrang Jaladri" Soekirman's work is one of the novels that tell the story about the Javanese diaspora's attitude or behavior. This essay will deliver the portrayal of the Javanese diaspora that expresses in the book. This essay is qualitative with the approach take-note-technique. The result of this study reveals Javanese, although living outside their area, will look for their origin like visiting the grave of their ancestor.